Determining Gravitational Acceleration with the Mathematical Pendulum Swing Method - Azmi, Valiant Zahirul; Hidayat, Dinnisa Haura Zhafira; Liaramadanty, Liaramadanty; Ambardhani, Muhammad Subhaan; Hidayat, Ahmad Farrel Al Falubi; Ahmad, Adnan; Febrilianto, Yogiek (Jurnal Info Sains : Informatika dan Sains, 2025)
Pendulum-derived gravitational acceleration values vary unpredictably due to unquantified string length and initial angle dependencies. This study aims to assess the feasibility and precision of the mathematical pendulum swing method in measuring gravitational acceleration. The research investigates the relationship between the pendulum’s string length, oscillation period, and initial deviation angle. It is hypothesized that longer strings will result in slower oscillations while shorter strings produce faster motions. Additionally, the study examines how these factors collectively impact gravitational acceleration measurement. Through controlled experiments, the study’s goal is to determine the precision of the pendulum swing method in determining gravitational acceleration and the factors influencing its reliability. Results demonstrate that a simple mathematical pendulum accurately determines gravitational acceleration with a calculated value of approximately 9.95974m/s². The findings confirm that the square of the oscillation period is directly proportional to the string length (T² ∝ l) and emphasize the importance of maintaining the initial deviation angle under 10 degrees to ensure measurement accuracy. These findings reinforce the pendulum’s utility in physics education and affordable gravitational field assessment, particularly in resource-limited settings. The study provides a foundational framework for improving experimental accuracy in classical mechanics and highlights the method’s enduring relevance in scientific pedagogy and fundamental research.